Substituted Dithiobiurets, their Molybdenum and Tungsten Complexes as Corrosion Inhibitors for Mild Steel in Sulphuric Acid - Rastogi,R.B. (2004)
The inhibition of mild steel corrosion in 1N sulphuric acid was studied in the presence of various concentrations (10-150 ppm) of substituted dithiobiurets and their molybdenum and tungsten complexes at 25 °C. All the compounds behaved as ambiodic corrosion inhibitors for mild steel and were considered to inhibit the corrosion by getting adsorbed on the surface. The inhibition efficiencies (IEs) of the complexes, in general, were found to be appreciably higher than those of corresponding ligands. However, the IE values of the complexes of molybdenum and tungsten of the same ligand did not differ much in their magnitude indicating thereby that the nature of central metal ions hardly influenced the inhibition efficiency. The slight difference in the IEs of the complexes at a given concentration seems to be caused by the slight difference in their size. The variation in IEs of different derivatives of ligands has been attributed to change in their size, number of active sites for adsorption and the electron density on these active sites. Scanning Electron Microscopy was used to study the surface of corroded and inhibited specimens.